Bibliotekinių procesų valdymo klausimu - Broniukaitis, Romualdas; Janulevičienė, Alma (Knygotyra, 1986)
Library as an object of management is investigated not enough, because of the complication of the system. In order to manage some process one needs information about its dimensions and tendencies of their alternation. At present various mathematical methods based on the statistical processing of library data, readers needs and information flows are used. That’s why the first step on the way to solve the problems of library management is statistical analysis of objective characteristics and regularities. The analysis of readers contingent would enable to constitute the mathematical model of library readers. Our investigation (on the basis of automatised subsystem of analysis and calculation „Periodika" in Republican Scientific Technical Library-1975-1981) enables to draw the following conclusions concerning the age of the readers: During the period 1975-1981 the readers contingent had become younger. Statistical distribution of readers is more asymmetrical in comparison with 1975. The summit of distribution sharpens. The main contingent of readers is 19-40 years old. That’s why the main problem is to satisfy their information needs. While creating the model of readers we suppose that the readers contingent distributes according to generalized beta-distribution. The analysis showed that with the probability over 0,95 the hypothesis is acceptable.